A retrospective review of hypertension control at Helen Joseph hospital over a 3 month period - Mohamed, Farzahna (My University, 2016)
Background: The 66% global increase of people diagnosed with hypertension (HT) from 1980 to 2008 highlights the devastating economic and medical implications on the health sector. Appropriate treatment of HT is an important strategy to reduce global cardiovascular (CV) risk. Objective: To determine the number of patients who achieved target blood pressure (BP) in accordance with the 2011 South African Hypertension Guidelines (SAHG). Secondary objectives were to assess compliance to the SAHG with regards to routine investigations carried out on patients and to compare differences between the controlled versus uncontrolled hypertensive groups with regards to demographics, body mass index (BMI), target organ damage (TOD), co-morbidities and therapy. Methods: The study was a retrospective clinical audit involving medical records of 300 patients with primary hypertension, who had been on antihypertensive treatment for a minimum of one year attending the specialised Hypertension Clinic at Helen Joseph Hospital (HJH) between 1st January and 31s March 2012. A questionnaire was designed to assess all the parameters required to meet the objectives. Results: The median age of the study population was 63 years, with a female predominance. This study showed that 49% of the study population achieved target BP. The prevalence of known diabetes, dyslipidaemia, TOD and chronic kidney disease (CKD) is 28%, 66%, 5%, and 11% respectively. The following variables were significantly higher in the uncontrolled BP group: age ≥ 65 years, hyperglycaemia, dyslipidaemia (specifically hypertriglyceridemia), obesity, elevated serum creatinine and proteinuria. Conclusion: The study showed that the total number of patients achieving target BP, as recommended by the 2011 SAHG, at a specialised HT clinic is suboptimal. Compliance to guidelines regarding routine investigations was suboptimal. This can be attributed to both patient, physician and facility related factors.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment for the degree of Master of Medicine Johannesburg 2016